Allelopathic Potential of Aerial and Root Extracts of Alfalfa Against Germination and Seedling Related Traits of Four Weed Species. - Rasool, Abdulsalam Abdulrahman (Sulaimani Journal for Pure and Applied Sciences, 2014)
In this study, we investigated the effect of aerial and root water extract of Alfalfa (Medicago sativa) plant on seed germination and seedling growth of four weed species. This study was carried out in the phytochemistry laboratory/Faculty of Agricultural Sciences/Sulaimani University. Factorial experiment conducted in Completely Randomized Design (CRD) with 3 replications, including five concentrations 2,4,6,8 and 10 g of aerial and root dry tissues of alfalfa (Medicago sativa L.) plants per 100ml of MeOH 70% v/v, against germination and seedling growth of four problematic weeds, which widely distributed in wheat fields, namely cephalaria (Cephalaria syriaca L.), rye grass (Lolium perenne L.), bitter vetch (Lathyrus linifolius L.) and black mustard (Brassica nigra L.). Results of experiment showed that extracts from dry tissue of aerial and root parts of alfalfa greatly inhibited seed germination and seedling growth of weeds at all concentrations compared to water control. Root extracts had the higher allelopathic potential toward imbibitions and germination of weeds compared to aerial extracts. Root extract reduced imbibitions by 61, 54, 61, 54 % and caused germination inhibition I%, by 51, 37, 34, and 47 % in cephalaria, rye grass, bitter vetch and black mustard respectively. Aerial extracts, significantly reduced hypocotyls, radicle length and dry weight compared to root extracts. The reduction of seedling traits of cephalaria, rye grass, bitter vetch and black mustard respectively due to aerial extracts compared to water control were 52, 52, 32, 35% hypocotyls length reduction, 41, 44, 33, 48% radicle length reduced, 58, 61, 64, 76% hypocotyls dry weight losses and 60, 57, 58, 77% were losses in radicle dry weight. Allelopathicity increased for aerial and root tissues with increase in concentrations and the greatest inhibition was 80% equally for imbibitions and I%, which obtained by 10g dry root tissue per 100 ml MeOH extract occurred in cephalaria, while 10 g dry aerial tissues per 100 ml MeOH extracts shows the highest inhibition percentages of hypocotyls length by 78% in rye grass, radicle length by 79% in cephalaria, hypocotyls dry weight and radicle dry weight by 90% both in black mustard.
Keywords: Allelopathy; Medicinal plants; Saponins; Phenolic compounds; Bioherbicides,problematic weeds